STUDI TENTANG MEMBANGUN LOYALITAS NASABAH JP BONDING ASURANSI JASARAHARJA PUTERA (Nasabah PT Asuransi Jasaraharja Putera di Semarang - Dewita, Isma (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2012)
The observations on the number of insurance customer of Jasaraharja Putra (JP) Bonding Insurance found that during theÂ 2008-2010Â period the number of customers who continue to use the JP bonding insurance is decreased and the trend of the number of customers who are not proceeding the JP Bonding insurance of Jasaraharja Putra in Semarang duringÂ 2008-2010Â has increased. Referring to the gap phenomenon, can be inferred the problem of customers loyalty in the Jasaraharja Putra Bonding insurance. Based on the empirical phenomenon found and research gaps of earlier studies, the research problem formulated in this study is â€œHow to build customer loyalty of Jasaraharja Putra Bonding insurance in Semarang?â€Research model developed in building the customer loyalty of the insurance involves three independent variables which include trust, corporate image, and quality of service. The data on these variables obtained through interviews using questionnaire with the insurance customers of JP Bonding Insurance in Semarang. Then the data is analyzed using Multiple Regression tests of SPSS program.Results of the multiple regression analysis test shows that trust has significant influence on customer loyalty of the JP Bonding insurance; the corporate image has significant effect on customer loyalty of the JP Bonding insurance; and quality of service has significant effect on customer loyalty of the JP Bonding insurance of PT Jasaraharja Putra Semarang.